Studi Komparasi Model Pembelajaran PBL dan modelPembelajaran PJBL terhadap Hasil Belajar IPAPada siswa kelas IV SDN IV Jatisrono danSDN II Jatisari Tahun 2015/201 - Nur Santi, Yuliani (2016)
This study aimed to: (1) differences in the influence of PBL models and PPA on the results of fourth grade students learn science Jatisrono IV SDN and SDN II Jatisari. (2) the effect of which is larger than the model PBL with PPA to the learning outcomes IPA IV grade IV SDN and SDN II Jatisrono Jatisari. This study uses a quantitative study with an experimental model. the subject of his research is the fourth grade students of SDN IV Jatisrono and SDN II Jatisari year 2015/2016. The data collection technique using the techniques of tests and documentation. Techniques of analysis using t tests were preceded by the prerequisite test analysis is the homogeneity test and test for normality. Based on data analysis with a significance level of 5% was obtained t_hitung> t_tabel, namely 3.844> 2.000 and the average - average results learn science class IV SDN IV Jatisrono with the model PPA and grade IV SDN II Jatisari model PBLadalah 76.00> 73.00. The conclusion of this study were (1) there are differences in the influence of the model PBL and PPA on learning outcomes IPA grade IV SDN IV Jatisrono and SDN II Jatisari (2) the model PPA greater influence than in the model PBL on learning outcomes ipa grade IV SDN IV Jatisrono and SDN II Jatisari.